PROFILE OF VOLATILE COMPONENTS IN COCOA BEANS (THEOBROMA CACAO) FROM HIGHLAND AND LOWLAND AREAS OF BANTAENG, SOUTH SULAWESI - Norman Hanif; Jumriah Langkong; Adiansyah Syarifuddin (jurnal1, 2020)
Volatile profiles of cocoa from highlands and lowlands have not been reported in scientific journals. Therefore, this study aims to determinethe volatile profiles of cocoa beans from highland and lowland regions. Cocoa beans were extracted using Maceration method and analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). The results of this study indicate that the highest free fatty acid content (FFA) of 7.18% was obtained in sample from the highland with 3 days of fermentation (A1B1), the highest water content (4.29%) was obtained incocoa beans sample from lowland with 5 days of fermentation (A1B2), the highest ash content (4.28%) was obtained in cocoa beans sample from lowland with 3 days of fermentation (A2B1), the highest protein content (13.32%)was obtained in sample from the highland with 5 days of fermentation (A1B2), and the highest fat content(49.85%)was obtained incocoa beans sample from lowland with 3 days offermentation. Another differentiating characteristic between cocoa beans from lowland and highland was the occurrenceofn-Hexadecanoic acid and 3,7-dimethyl-3,7-dihydro-1h-purine-2,6-dione- in samples from lowland.